Diagnosis and treatment of anemia (New York States Academic Press, 2023)
Anemia is a blood disorder, where the capability of the blood to carry oxygen is decreased due to a low blood count, or due to low levels of hemoglobin. Chronic anemia has symptoms such as weakness, headaches, tiredness and short breath, while acute anemia shows symptoms like loss of consciousness, confusion, dizziness and increased thirst. The causes of anemia include loss of blood, fluid overload, impaired production of red blood cells, and increased reduction of red blood cells. Anemia is diagnosed on the basis of complete blood count. A blood test is utilized generally for determining the platelets and count of red blood cells and white blood cells. Tests such as serum ferritin, serum vitamin B12, and sample of bone marrow can help in determining the type of anemia and its cause. Treatment of anemia is dependent on its severity and cause, and includes iron supplementation in oral and injectable form, blood transfusions, intramuscular injections of vitamin B12, hyperbaric oxygen, and erythropoiesis-stimulating agents. This book aims to understand the diagnosis and treatment of anemia. It will serve as a reference to a broad spectrum of readers.
Keywords: Anemia; Animea-Pathophysiology; Anemia- Disgnosis & Treatment; Blood- Diseases; Pratt, Martha ed